Early recovery of pulmonary vein conduction after cryoballoon ablation for paroxysmal atrial fibrillation: a prospective study - Chierchia, Gian Battista; de Asmundis, Carlo; Müller-Burri, Stephan-Andreas; Sarkozy, Andrea; Capulzini, Lucio; Paparella, Gaetano; Chierchia, Sergio; Roos, Markus; Brugada, Pedro (Europace, 2009)
Aims To assess the incidence of early pulmonary vein (PV) reconnection, characterize the anatomic features of the reconducting veins, and analyse the time course of their recovery in a series of consecutive patients with paroxysmal atrial fibrillation (AF) undergoing ablation with the Arctic Front Cryoballoon. Methods and results We prospectively enrolled 26 patients (20 males; age 55.4 ± 4.1) for circumferential PV cryoballoon isolation for highly symptomatic paroxysmal AF. Following isolation of all veins, we analysed PV potentials in each vein after 30 and 60 min with a circular mapping catheter. After successful electrical isolation of all 104 PV’s, recurrence was observed only in three veins (2.8%) after 30 min. Two further cryoballoon applications in each of these veins lead to their isolation. These veins were still electrically disconnected at 60 min. No PV reconnection was observed in any of the other 101 veins (97.1%) at 30 and 60 min. Conclusion Cryoballoon ablation of the PV’s ostia is a very effective technique to achieve electrical isolation, with a very low rate of early reconnection.